2022
DOI: 10.1186/s13756-022-01183-y
|View full text |Cite
|
Sign up to set email alerts
|

The in situ efficacy of whole room disinfection devices: a literature review with practical recommendations for implementation

Abstract: Background Terminal cleaning and disinfection of hospital patient rooms must be performed after discharge of a patient with a multidrug resistant micro-organism to eliminate pathogens from the environment. Terminal disinfection is often performed manually, which is prone to human errors and therefore poses an increased infection risk for the next patients. Automated whole room disinfection (WRD) replaces or adds on to the manual process of disinfection and can contribute to the quality of termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 117 publications
0
0
0
Order By: Relevance
“…Enterococcal antimicrobial resistance and virulence underscore the importance of controlling these microorganisms' diffusion, especially among the hospital recovered patients. Reccomandation for controlling VRE involve isolating individuals with current or past VRE colonization, using protective gown and gloves, hand hygiene with antiseptic post glove removal, and allocating dedicated equipment like stethoscopes for VRE-colonized patient rooms [207]. Additionally, precautions should be taken to avoid touching environmental surfaces (e.g., doorknobs) after glove removal.…”
Section: Prevention and Infection Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococcal antimicrobial resistance and virulence underscore the importance of controlling these microorganisms' diffusion, especially among the hospital recovered patients. Reccomandation for controlling VRE involve isolating individuals with current or past VRE colonization, using protective gown and gloves, hand hygiene with antiseptic post glove removal, and allocating dedicated equipment like stethoscopes for VRE-colonized patient rooms [207]. Additionally, precautions should be taken to avoid touching environmental surfaces (e.g., doorknobs) after glove removal.…”
Section: Prevention and Infection Control Strategiesmentioning
confidence: 99%
“…Additionally, precautions should be taken to avoid touching environmental surfaces (e.g., doorknobs) after glove removal. Enhanced environmental cleaning methods may be recommended due to documented instances of persistent VRE presence in hospital rooms despite standard cleaning procedures [207,208]. Recent studies have demonstrated that decolonization through the use of chlorhexidine gluconate bathing for patients in Intensive Care Units (ICU) can prevent hospital-acquired infections and reduce the acquisition rate of MDR organisms including VRE [209]; this could be a potentially interesting path to follow for wards characterized by the presence of immunocompromised patients.…”
Section: Prevention and Infection Control Strategiesmentioning
confidence: 99%